Clinical value of pulmonary congestion detection by lung ultrasound in patients with chronic heart failure. Issue 11 (1st October 2021) - Li, Na; Zhu, Yunlong; Zeng, Jianping
Abstract: Chronic heart failure is one of the common causes of hospitalization and death. Pulmonary congestion is the common disease feature of patients with chronic heart failure, which could be correctly diagnosed by lung ultrasound. Efficacy of lung ultrasound‐guided pulmonary congestion management for patients with acute heart failure is well documented, however, more evidence is needed to establish the clinical value of pulmonary congestion detection by lung ultrasound examination in patients with chronic heart failure. This review summarized current evidence related to the use and clinical value of pulmonary congestion assessment by lung ultrasound in patients with chronic heart failure, aiming to provide new suggestions on promoting the widespread use of lung ultrasound in patients with chronic heart failure to improve the quality of life and outcome of patients with chronic heart failure.